Financial management practices of UP students - Antonio, Wella M.; Gabriel, Florenda S. (2004.)
This research was a descriptive study on the financial management practices of UP Students. Its primary objective was to determine the financial management practices of UP undergraduate students allocated their allowance and other sources of income. And lastly, this research identified students' needs for financial management education. The survey method was used in this study. Fifty-eight survey questionnaires were distributed to an convenience sample of students coming from different colleges of the University of the Philippines, Diliman campus. Data were analyzed using frequency distribution and measures of central tendency. This research found out that the UP Students got an average allowance of PhP 1,250 weekly from their parents. Average UP student spent PhP 1,274 weekly. Topping the list of their expenses was food, and surprisingly prepaid cards came second. Most of the respondents turn to their parents as a source of financial information. Majority (68 percent) of the respondents indicated that they budgeted their money. However, a bigger proportion (82 percent) borrowed money from friends and more than half (58 percent) of the respondents had outstanding loans. Twelve percent of the respondents had a personal credit card account. This emphasized the critical part played by the family in building the foundation of financial management skills. This study also revealed that UP students would like to learn the following: how to get the best value for their money, banking, credit card, different forms of savings, and insurance. Results showed that there is a need for UP students to learn more financial management skills. Thus, this research suggests that financial management should be emphasized in the relevant college courses students take.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Finance, Personal